The Development of a Design and Construction Process Protocol to Support the Home Modification Process Delivered by Occupational Therapists - Rachel Russell; Marcus Ormerod; Rita Newton (Journal of Aging Research, 2018)
Modifying the home environments of older people as they age in place is a well-established health and social care intervention. Using design and construction methods to redress any imbalance caused by the ageing process or disability within the home environment, occupational therapists are seen as the experts in this field of practice. However, the process used by occupational therapists when modifying home environments has been criticised for being disorganised and not founded on theoretical principles and concepts underpinning the profession. To address this issue, research was conducted to develop a design and construction process protocol specifically for home modifications. A three-stage approach was taken for the analysis of qualitative data generated from an online survey, completed by 135 occupational therapists in the UK. Using both the existing occupational therapy intervention process model and the design and construction process protocol as the theoretical frameworks, a 4-phase, 9-subphase design and construction process protocol for home modifications was developed. Overall, the study is innovative in developing the first process protocol for home modifications, potentially providing occupational therapists with a systematic and effective approach to the design and delivery of home modification services for older and disabled people.